A SOCIO-LEGAL ANALYSIS OF ACQUITTALS UNDER THE NARCOTIC DRUGS PSYCHOTROPIC SUBSTANCES ACT (CAHIERS MAGELLANES-NS, 2024)
The Narcotic Drugs and Psychotropic Substances Act, 1985 is a prominent socio legal law for the reason that it causes a damage not only to the society at large but it also poses a threat to the life of people, social order and even the danger to the international peace and order Socio legal laws are in general different from the normal criminal laws for the reason of their broad dimensions of causing a great harm to the society at large. Such a damage may be to social and economic health of the society. In this category The Narcotic Drugs and Psychotropic Substances Act, 1985is more serious a law and, therefore, it needs special dealing by the law makers and its administrators. It was in this background that The Narcotic Drugs and Psychotropic Substances Act, 1985was enacted in the year 1985[1] providing there under more stringent punishments going up to 20 years of imprisonments, provisions for minimum punishment to the tune of 10 years and getting such imprisonments, which include heavy fines, getting multiplied by 1.5 times of the punishments in repeated cases[2]. Furthermore, as in the case of socio-economic offences, the mens rea is not required to be proved, but presumptions in this regard are recognized, thereby causing an onus on the accused to prove his innocence[3]. The object of this Act is to snub the trade of narcotic drugs and psychotropic    substances so as to avoid menace of drug abuse[4]. With this end in view, the law provides for special provisions to deal with the perpetrators of this crime with iron hands. The presumptions of commission of the offence are also aimed at ensuring the conviction of all criminals under The Narcotic Drugs and Psychotropic Substances Act, 1985. But contrary to this assumption, when these researchers gathered firsthand information of convictions under The Narcotic Drugs and Psychotropic Substances Act, 1985, they were surprised to see that there were large scale acquittals[5] as well whereby the trade of narcotic drugs was continuing unabated and increasing its proportions, resultantly taking away vitality of Punjab youth[6]. With an objective to identify the reasons for such acquittals contrary to the objective of law, the researchers conducted an analytical study of the decided cases in the district of Kapurthala and interviewed leading Advocates dealing with such cases .The sample of this paper turns to be an analytical study of 80 case files relating to the district Kapurthala which have been decided in last three years. Such files were collected from 4 leading Advocates having handled these cases i.e. 20 files from each Advocate. To seek clarification from the point of acquittal, all these 4 Advocates were interviewed by researchers and the information thus collected given in the shape of this article [1] The Statement of Objects and Reasons of The Act, 1985 not only underscored it but also reiterated the same in Amendment Acts of 1989, 2001 and 2014. Clause (2) of the objects and reasons (1985 Act) provided”2. In view of what has been stated above ------------- India has become a party.”In 1989 Amendment Act again emphasized in the opening paragraph of objects and reasons: “in recent years: ------the need to amend the law further strengthen it was felt”[2] Sections 15to40 provide for penalties under the Act marking a sensible difference between different kind of narcotic drugs and psychotropic substances and also variations for recovery of small quantities, understandably for personal use of addicts, and the commercial quantities. In the case of latter, the punishment normally goes to 20 years of imprisonment and heavy fines from 1-2 Lakh rupees. Sections also prescribe for minimum punishment of 10year imprisonment[3] Section 54 of the Act provides for this as under: 54 presumption from possession of illicit articles- in trial under this Act, it may be presume, unless and until the contrary is proved, that the accused has committed an offence under this Act in respect of----Any narcotic drug or psychotropic substance or controlled substance;Any opium poppy, cannabis plant or coca plant growing on any land which he has cultivated;Any apparatus specially designed or any group of utensils specially adopted for the manufacture of any narcotic drugs or psychotropic substances or controlled substances; orAny materials which have undergone any process towards the manufacture of a narcotic drug or psychotropic substance or controlled substance, or any residue left of the materials from which any narcotic drug or psychotropic substance or controlled substance has been manufactured, for the possession of which he fails to account satisfactorily.Section 35of the Act  also clarified: Presumption of culpable mental state.-(1) In any prosecution for an offence under this Act which requires a culpable mental state of the accused, the Court shall presume the existence of such mental state but it shall be a defence for the accused to prove the fact that he had no such mental state with respect to the act charged as an offence in that prosecution.Explanation.-In this section "culpable mental state" includes intention, motive knowledge of a fact and belief in, or reason to believe, a fact.The supreme court has also underlined the importance of Section 35 in its judgements, vig; karnail singh vs state of Rajasthan 2000 crilj9636: Madan Lal v state of Himachal Pradesh,AIR 2003 SC3542. [4] Supra note 1.the Apex court in Raj kumar vs Union of India, 1991 outlined objective of the Act and referred to the gravity of drug problem having international dimensions and the crimes being against entire society which must be dealt with iron hands  [5] The acquittal rate in our society has come to 32.5% and in good many cases it is only on technical grounds.[6] Newspaper reports:Anshu Jain, “United Nation and Drug Abuse Control” In Singh  -----------     ,P. 260 writes:                                                                        The Supreme Courts the recent judgment of union of India V. Mohan lal and another (2016) observes Under Para16:”The menance of drugs in this country has alarming dimensions and proportions. Studies been on conferences and seminars have very often shown that the menance is deep rooted not only because drug lords have the many power and transnational links but also because the enforcement agencies like the police and at whims of politicians in power help them in carrying on what is known to be a money spinning and flourishing trade”Earlier, the Constitution bench of Supreme Court in Baldev Singh mentioned the ill effects of drug abuse, arising out of vitiating The Narcotic Drugs and Psychotropic Substances Act, 1985 as: “Drug abuse the social . While  drug addiction eats in the vitals of the society, drug trafficking not only eats into the vitals of the economy of a country, but illicit money generated by the drug trafficking is often used for  illicit activities including encouragement of terrorism……”